IMPLEMENTASI MEDIA AUDIOVISUAL TERHADAP KEAKTIFAN BELAJAR AKIDAH AKHLAK DI KELAS V MI MA’HAD AL-ZAYTUN - Firdaus, Ridwan; Mardani, Dadan; Iswandi, Irvan (Cahaya Ilmu Bangsa Institute, 2024)
This research was conducted at MI Ma'had Al-Zaytun, Indramayu, using qualitative research methods to obtain data. The data collection techniques used include observation, interview, and documentation. Data analysis was done by data reduction, data presentation, and conclusion drawing. The results showed that the implementation of audio-visual learning media succeeded in increasing the learning activeness of Akidah Akhlak fifth grade students at MI Ma'had Al-Zaytun. This is evident from the increase in student participation in asking questions and discussing, as well as students' sense of responsibility for the material provided by the teacher. This has a significant positive impact in increasing student activeness. The conclusion of this study is that the implementation of audiovisual learning media in Akidah Akhlak learning in class V-B-05 MI Ma'had Al-Zaytun is very instrumental in increasing student activeness during the learning process. And the supporting and inhibiting factors of audiovsisual media include the availability of adequate learning media, teachers who are skilled and experienced in utilizing learning media, as well as creative and innovative learning methods, such as the use of learning videos and animations. And the inhibiting factors include technical problems such as internet connection interruptions or device damage that can hinder the smooth learning process based on audiovisual media. Key Words: Implementation of audi visual media, student activeness